2017
DOI: 10.18632/oncotarget.16395
|View full text |Cite
|
Sign up to set email alerts
|

Tumor physiological changes during hypofractionated stereotactic body radiation therapy assessed using multi-parametric magnetic resonance imaging

Abstract: Radiation therapy is a primary treatment for non-resectable lung cancer and hypoxia is thought to influence tumor response. Hypoxia is expected to be particularly relevant to the evolving new radiation treatment scheme of hypofractionated stereotactic body radiation therapy (SBRT). As such, we sought to develop non-invasive tools to assess tumor pathophysiology and response to irradiation. We applied blood oxygen level dependent (BOLD) and tissue oxygen level dependent (TOLD) MRI, together with dynamic contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
3
29
1
Order By: Relevance
“…We previously reported a typical BOLD signal response of 2% to 3% for subcutaneous A549 compared with the 8% to 10% observed in the orthotopic setting using the same pulse sequence, though with the different TE required to match the observed T2*. A more rigorous comparison is R2*, which indicated ~120 s –1 for orthotopic A549 tumors here versus 58 s –1 for subcutaneous tumors . We note that some values are greater than typically reported for tumors previously, but previous studies of subcutaneous tumors reported a mean value of 101.4 s –1 for G3H prolactinomas (with a range of 75–140 s –1 ) and values as high as 110 s –1 for DU‐145 tumors and 130 s –1 for PC3 tumors at 4.7T .…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…We previously reported a typical BOLD signal response of 2% to 3% for subcutaneous A549 compared with the 8% to 10% observed in the orthotopic setting using the same pulse sequence, though with the different TE required to match the observed T2*. A more rigorous comparison is R2*, which indicated ~120 s –1 for orthotopic A549 tumors here versus 58 s –1 for subcutaneous tumors . We note that some values are greater than typically reported for tumors previously, but previous studies of subcutaneous tumors reported a mean value of 101.4 s –1 for G3H prolactinomas (with a range of 75–140 s –1 ) and values as high as 110 s –1 for DU‐145 tumors and 130 s –1 for PC3 tumors at 4.7T .…”
Section: Discussionsupporting
confidence: 43%
“…We note that some values are greater than typically reported for tumors previously, but previous studies of subcutaneous tumors reported a mean value of 101.4 s –1 for G3H prolactinomas (with a range of 75–140 s –1 ) and values as high as 110 s –1 for DU‐145 tumors and 130 s –1 for PC3 tumors at 4.7T . We are unaware of other studies of orthotopic lung tumors using oxygen‐sensitive MRI, although other studies have examined human lung tumor xenografts growing subcutaneously in rats and mice …”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Hyperoxic gas breathing interventions are generally reversible and studies have shown that repeated challenges resulted in similar responses, allowing effective comparison of hypoxia‐modulating interventions . Successive imaging on sequential days or over several days showed no significant differences in responses in some tumor types . A change in longitudinal relaxation in response to an oxygen‐breathing challenge has been shown to discriminate tumor tissue from radiation‐induced necrosis .…”
Section: Quantitatively Interrogating Biologymentioning
confidence: 99%